Status kesuburan tanah, aplikasi pupuk petroganik + NPK terhadap pertumbuhan jagung pulut merah genotipe Unipa di Distrik Waibu Kabupaten Jayapura - Datu L. Palulun; Irnanda A. F. Djuuna; Purbokurniawan Purbokurniawan; Alce Ilona Noya; Nouke L. Mawikere (Cassowary, 2023)
Soil fertility status was an important factor that determines the success of corn farming. The five properties used to predict this fertility status are C-Organic, KB, P2O5 – total, K2O – total, and CEC. The combination of the use of organic and inorganic fertilizers aims to improve soil fertility, increase productivity, and soil sustainability. The study used a 2-factor randomized block design. The first factor was the combination of fertilization consisted of 6 levels and the second factor was 2 genotypes of red corn pulut Unipa. The results showed that the soil fertility status at the study site was classified as low with the details of the criteria of C-Organic (Low), KB (High), P2O5 (High), K2O (High), and CEC (Low). There were no interaction in all growth components. The genotype of Anggi Merah Pulut Unipa 3 had better growth than Anggi Merah Pulut Unipa 1.